Characterization of the temperature sensitive phenotype of the A/Ann Arbor/6/60 cold-adapted virus and its recombinants. - Murphy, B R (1981)
The A/Ann Arbor/6/60 cold-adapted (ca) donor virus had a 38 degrees C shutoff temperature when tested in MDCK tissue culture. ca recombinant viruses bearing all six "internal genes" of the A/Ann Arbor/6/60 ca donor virus and the surface antigens of wild-type virus can manifest a 1,000-fold difference in plaquing efficiency at 38 degrees C. These observations suggest that the A/Ann Arbor/6/60 ca donor genes that specify the temperature sensitive phenotype of the ca recombinants can undergo genetic modification during the production and passage of the recombinants. The NS gene in the ca recombinant virus could be inherited from either parent without influencing the level of temperature sensitivity of the ca recombinant.